Politeness Behavior in Social Interaction in Terms of the Level of Interest in Playing Online Games - Indri Anugrah Ramadhani; Asrul Asrul; Fauda Arni Wimbri (Lectura : Jurnal Pendidikan, 2023)
Students in the current era prioritize playing online games over social interaction, so it impacts deviant social behavior for adolescents, especially those addicted to playing online games. This study aims to analyze politeness behavior in social interaction in terms of students’ level of interest in playing the Garena Free Fire game. This study uses a qualitative method with a case study approach. Data collection techniques include: observation of students and parents, interviews with students and parents, and documentation. The research population were Grade V and VI Sekolah Dasar (SD) Muhammadiyah Majaran Kabupaten Sorong, with six students and six parents/guardians. The study’s findings obtained observational data that two students did not show the aspect of speaking ethics while the other four students responded sufficiently, the aspect of responding to questions there were four students and two other students were quite good. Three students and three others did not respond in obeying their parents’ orders. The habitual aspect of laughter is two students; the other four could be more responsive. This shows that the hobby of playing the Garena free fire game for students does not all have a bad impact on polite social interaction behavior but also has a positive effect. Furthermore, interviews were conducted with six parents/guardians of students, and found that all parents/guardians provided the opportunity to play games with various agreements. This study concluded that the hobby of playing Garena Free Fire online games has a positive and negative role in politeness behavior in terms of the social interaction.